Comparative performances of microalgal-bacterial co-cultivation to bioremediate synthetic and municipal wastewaters whilst producing biodiesel sustainably - Leong, W.H. (MDPI AG, 2020)
The potentiality of a microalgal-bacterial culture system was explored in bioremediating wastewater while generating biomass for biodiesel production. A pre-determined optimal activated sludge and microalgal ratio was adopted and cultivation performance was evaluated in both synthetic and municipal wastewater media for nitrogen removal along with biomass and lipid generation for biodiesel production. The microalgal-bacterial consortium grown in the municipal wastewater medium produced higher biomass and lipid yields than those in the synthetic wastewater medium. The presence of trace elements in the municipal wastewater medium, e.g., iron and copper, contributed to the upsurge of biomass, thereby leading to higher lipid productivity. Both the microbial cultures in the synthetic and municipal wastewater media demonstrated similar total nitrogen removal efficiencies above 97. However, the nitrification and assimilation rates were relatively higher for the microbial culture in the municipal wastewater medium, corresponding to the higher microbial biomass growth. Accordingly, the feasibility of the microalgal-bacterial consortium for bioremediating real municipal wastewaters was attested in this study by virtue of higher biomass and lipid production. The assessment of fatty acid methyl esters (FAME) composition showed the mixed microbial biomasses comprised 80â93 C16 to C18 FAME species, signifying efficient fuel combustion properties for quality biodiesel requirements. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.